2008
DOI: 10.1097/mao.0b013e31817f73af
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Serum Eardrops Therapy With a Chitin Membrane for Closing Tympanic Membrane Perforations

Abstract: Autologous serum eardrops therapy with a chitin membrane, which requires no surgical intervention, was found to be a promising office-based technique for the closure of chronic TM perforations because of its ease, safeness, and feasibility. However, additional studies are needed to independently analyze the specific benefits of the serum drops and the chitin membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 15 publications
0
23
0
1
Order By: Relevance
“…Recently, Kakehata et al reported good results by using a new treatment for closing chronic TM perforation using autologous serum [18]. Both autologous serum and umbilical cord serum owe their efficacy to the presence of various growth factors, like EGF, acidic and FGF, PDGF, hepatocyte growth factor, vitamin A, transforming growth factor (TGF)-␤, substance P, insulin-like growth factor (IGF)-1, nerve growth factor (NGF), fibronectin, and serum antiproteases, such as ␣2-macroglobulin [19][20][21].…”
Section: Article In Pressmentioning
confidence: 97%
“…Recently, Kakehata et al reported good results by using a new treatment for closing chronic TM perforation using autologous serum [18]. Both autologous serum and umbilical cord serum owe their efficacy to the presence of various growth factors, like EGF, acidic and FGF, PDGF, hepatocyte growth factor, vitamin A, transforming growth factor (TGF)-␤, substance P, insulin-like growth factor (IGF)-1, nerve growth factor (NGF), fibronectin, and serum antiproteases, such as ␣2-macroglobulin [19][20][21].…”
Section: Article In Pressmentioning
confidence: 97%
“…The perforations were closed spontaneously or with a chitin sheet patch in most patients. For 12 patients, autologous serum ear drops and/or basic fibroblast growth factor with a chitin sheet patch therapy in the outpatient clinic [Kakehata et al, 2008] were performed and the perforations were closed successfully except in 1 patient. Small perforations remained in 2 patients.…”
Section: Side Effectsmentioning
confidence: 99%
“…[26][27][28] Autologous serum has been used over the last two decades to promote the healing of epithelial and cartilaginous damage of both known and unknown aetiologies. 13,[29][30][31] At the same time, it includes various immunoglobulins (e.g. immunoglobulin G and immunoglobulin A) and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were centrifuged for 5 minutes at 3000 revolutions per minute. 13 The resulting serum was placed in a dental syringe and stored at 4°C. In order to create ototoxicity, amikacin (Amikozit; EczacibasiZentiva, Istanbul, Turkey) was administered at a dose of 0.2 cc (80 mg/ml) via the intratympanic and intramuscular routes, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation